Rethinking military history - Black, Jeremy (Routledge, 2004)
Rethinking Military History is a bold new 'thought book' that reconsiders military history at the beginning of the twenty-first century. The chapters provide a valuable and concise survey of the main themes in the study of military history from 1500 to the present day as Jeremy Black reveals the main trends in the practice and approach to military history and proposes a new manifesto for the subject to move forward. This must-read study demonstrates the limitations of current approaches, including common generalizations, omissions, and over-simplications. Engaging the.